THE STUDENT’S ABILITY IN IDENTIFYING TYPES OF ADJECTIVES; ENGLISH TRANSLATION OF SURAH LUQMAN - Widhya Nusantari; Dewi Suryani Djamdjuri; Enni Erawati Saragih (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2018)
Mastery over words helps leaner English to communicate their emotions and purpose more effectively. Grammatical ability is how English leaner understanding grammar lesson. It also can identify the adjective is one of the must have capabilities by students. In this research, the researcher used worksheet to find out students’ ability in identifying adjectives Qur’an surah Luqman verse 13 until 19. This research was conducted at Islamic Education Faculty of Ibn Khaldun University, Pendidikan Guru Madrasah Ibtidiyah (PGMI) Department. Qualitative research method used in this study. The result of this research shows that the ability of students can be concluded that students’ ability to identify adjectives is still medium. From the nine adjectives found in surah Luqman English translation verse 13 until 19, the highest number is six. The students of PGMI can learn English by using Qur’anic verses about education that has been translated in English, this also the same with all surah in the noble Al- Quran. So that it is recommended to use any part of the noble Qur’an as teaching media specially reading and structure. Using English translation of noble Qur’an will make students add vocabulary and learn more about language.